Efficacy and safety of janagliflozin as add‐on therapy to metformin in Chinese patients with type 2 diabetes inadequately controlled with metformin alone: A multicentre, randomized, double‐blind, placebo‐controlled, phase 3 trial. Issue 3 (12th December 2022) - Gao, Leili; Cheng, Zhifeng; Su, Benli; Su, Xiuhai; Song, Weihong; Guo, Yushan; Liao, Lin; Chen, Xiaowen; Li, Jiarui; Tan, Xingrong; Xu, Fangjiang; Pang, Shuguang; et al.
Abstract: Aim: To evaluate the efficacy and safety of janagliflozin in Chinese patients with type 2 diabetes (T2D) inadequately controlled with metformin monotherapy. Materials and methods: This multicentre phase 3 trial included a 24‐week, randomized, double‐blind, placebo‐controlled period, followed by a 28‐week extension period. Patients (N = 421) with HbA1c of 7.0% or higher and 10.5% or less were randomized (1:1:1) to receive once‐daily placebo, janagliflozin 25 or 50 mg. After the 24‐week treatment period, patients on placebo were re‐randomized (1:1) to janagliflozin 25 or 50 mg for the additional 28‐week treatment, whereas patients on janagliflozin maintained the same therapy. The primary endpoint was the change from baseline in HbA1c to week 24. Results: At week 24, the placebo‐adjusted least squares mean changes of HbA1c were –0.58% and –0.58% with janagliflozin 25 and 50 mg, respectively ( P < .0001 for both). The proportion of patients achieving HbA1c less than 7.0% was higher with janagliflozin 25 and 50 mg compared with placebo (41.8%, 41.7% and 28.0%, respectively). Both janagliflozin doses provided significant reductions in fasting plasma glucose, 2‐hour postprandial glucose, body weight and systolic blood pressure, and improvements in high‐density lipoprotein cholesterol and insulin sensitivity compared with placebo ( P < .05 for all). The trends in improvement of these variables were retained during the 28‐week extension period. No severe hypoglycaemia occurred throughout the whole 52‐week treatment. Conclusions: Janagliflozin 25 or 50 mg once‐daily added to metformin therapy significantly improved glycaemic control, reduced body weight and systolic blood pressure, improved high‐density lipoprotein cholesterol and insulin sensitivity, and was generally well‐tolerated by Chinese T2D patients who had poor glycaemic control with metformin monotherapy.